Analisis Dan Perancangan Sistem Informasi Pelacakan Lulusan Berbasis Website - Edi Susena; Norma Puspitasari; Ayu Nur Laila Lutfi (LPPM Politeknik Jambi, 2020)
SMK Negeri 1 Pedan Klaten is a school that has been around for a long time and has many graduates. Tracking graduates are still carried out in one direction, namely by filling out forms. The data obtained is then entered in the graduate ledger. This has resulted in not maximally handling graduates. Current graduate data cannot be used as a benchmark for knowing the activities and whereabouts of graduates. The current solution that is considered to improve graduate data is by developing a graduate tracking information system. Data collection methods used were observation, interviews, documentation and literature study. The method of developing the system uses the Waterfall Model. Programming language is a Web programming language using Sublimetext and CSS text editors to create and edit and design. The databases used are PhpMyadmin and MySQL. The conclusion of this research is that the author has succeeded in analyzing and developing a graduate tracking information system in SMK Negeri 1 Pedan Klaten, the system is made by two users, namely admin and graduates. Admin can perform system management, while graduates can enter their current condition through this developed system. The system can make reports on the results of tracking graduates, the system can make it easy to search for graduate data.